Spectral‐Energy Efficiency Tradeoff in Mixed‐ADC Massive MIMO Uplink with Imperfect CSI. Issue 3 (1st May 2019) - Ding, Qingfeng; Jing, Yindi
Abstract : An uplink multi‐user massive Multi‐input multi‐output (MIMO) system is considered with a mixed Analog‐to‐digital converter (ADC) architecture under imperfect Channel state information (CSI). A closed‐form approximation for the Spectral efficiency (SE) is derived for a general mixed ADC structure with any resolution profile. To achieve a balance between the SE and receive Energy efficiency (EE) of the system, the ADC resolution profile optimization problem that maximizes a linear combination of the SE and the Base station (BS) receive power consumption is formulated. An algorithm based on gradient search is proposed whose complexity is linear in the number of BS antennas. Numerical results verify that the proposed ADC resolution design largely outperforms the two‐level structure especially in the lower SE region and provides more choices than the uniform‐ADC architecture for resolving the SE‐EE tradeoff.